Evaluasi Penggunaan Eritropoetin (EPO) yang dikaitkan dengan Clinical Outcome pada Pasien Hemodialisis di RSUP Prof. R. D . Kandou Manado. - Rambi, Firly Kartika Yuni; Ramatillah , Diana Laila (Journal of Pharmaceutical and Sciences, 2025)
Background: Chronic kidney disease (CKD) is a health issue that occurs in almost all parts of the world, and the number of patients continues to increase. CKD patients undergoing hemodialysis often experience anemia, which affects their quality of life and increases the risk of morbidity and mortality. Erythropoietin (EPO) is used to treat anemia, but its effectiveness can be affected by nutritional status, combination therapy, and other factors. Objective: To determine the profile of EPO therapy in CKD patients at the Dahlia Hemodialysis Unit at RSUP Prof. Dr. R.D. Kandou. Methods: An observational study with a retrospective cohort design (January–December 2020 with follow-up until December 2024) and a prospective design (October–December 2024). Patient medical records were processed and analyzed descriptively and analytically using Independent T-Tests, ANOVA, ANCOVA, and Kaplan-Meier survival analysis. Results: 209 patients undergoing therapy, 109 male (52.15%) and 100 female (47.85%). The average increase in post-treatment hemoglobin levels (Hb Post) compared to pre-treatment levels (Hb Pre) was 16.28%. Independent T-Test showed no significant difference in Hb levels between males and females (p>0.05). ANOVA Test showed a significant difference in Hb Post levels between age groups (F(7,201)=3.517; p=0.001). ANCOVA analysis showed that Hb Pre was the primary predictor of Hb Post (F=161.151; p<0.001). Conclusion: EPO therapy increases hemoglobin levels in CKD patients, with the response influenced by age and Hb Pre, but not by gender. Hb Pre levels are the primary predictor of treatment success.